State-Owned Enterprises and the Low-Carbon Transition - Prag, Andrew (OECD Environment Working Papers, 2018)
This paper explores the role of state-owned enterprises (SOEs) in the low-carbon transition in OECD and G20 countries. It tracks GHG emissions and energy investments by SOEs and analyses the impact of SOEs on investments in renewable electricity. A descriptive analysis of SOEs' role in the electricity sector shows the continued importance of SOEs, including prominent investments in both renewables and fossil-fuel-based electricity generation..